Microwave devices and circuits - Liao, Samuel Y. (New Delhi : Prentice Hall of India, 2004)
Engineering
Keywords: Microwave devices; Microwave system; Microwave transmission; Microwave waveguides; Microwave components; Transit-time devices; Strip lines